Biomass: biorefinery as a model to boost the bioeconomy in Costa Rica, a review - Rodolfo A Hernández-Chaverri (Universidad de Costa Rica, 2021)
Introduction. The lignocellulosic biomass that comes from agricultural residues, crops dedicated to wood energy, lignocellulosic biological residues as food by-products, kitchen scraps from homes, restaurants, and commercial premises, as well as cultivated algae, can be considered raw materials for the development of the bioeconomy. Since its composition is mainly based on cellulose, hemicellulose, and lignin; they can be used to produce various value-added products from bio-construction blocks in integrated bio-refinery processes. Objective. To stablish the importance of using biomass as a raw material for its incorporation in circular economy models in biorefinery processes, such as considerations of biomass management and pretreatment of biomass, the intrinsic potential for obtaining substances of commercial value depending on the carbon chain. Development. Approximately 90 % of lignocellulosic dry matter consists of cellulose (30-60 %), hemicellulose (20-40 %), and lignin (10-25 %) interrelated in a heteromatrix, while the remainder consists of ash and extracts. It is estimated that the biomass-based power generation potential in Costa Rica ranges close to 600 MW and active projects that generate about 122 MW have been identified. Conclusion. The use of biomass is an important element to be incorporated into the production of bioenergy and the development of a renewable chemical industry that leads to the achievement of objectives framed in the development of a bio-economic model, where Costa Rica has begun its parallel incursion to the advance of the 21st century.